2020
DOI: 10.1016/j.jcv.2020.104645
|View full text |Cite
|
Sign up to set email alerts
|

A comparative evaluation between the Abbott Panbio™ COVID-19 IgG/IgM rapid test device and Abbott Architect™ SARS CoV-2 IgG assay

Abstract: Introduction Antibodies to SARS-CoV-2 serve as critical diagnostic markers for determining how broadly the COVID-19 pandemic has spread, confirming patient recovery, monitoring potential long-term effects of infection, and evaluating potential protection from reinfection. As new antibody tests become available, it is important to evaluate their performance and utility. The aim of this study was to compare the performance of the Abbott Panbio TM COVID-19 IgG/IgM Rapid Tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 22 publications
3
32
3
Order By: Relevance
“…Thus, serological tests did not adequately indicate SARS-CoV-2 infection in patients with a previous positive NST result (IgM and IgG sensitivity of 27.78% and 50.00%, respectively). These results are in contrast to those from Batra and colleagues ( Batra et al, 2020 ), who found that the test had a specificity of 100% and sensitivity of 99.1% for specimens collected >14 days post symptom onset or >5 days post-RNA testing. On the other hand, Meschi et al (2020) showed that the Abbott system could have lower sensitivity, which is more similar to our results (61.9% on the fourteenth day).…”
Section: Discussioncontrasting
confidence: 99%
“…Thus, serological tests did not adequately indicate SARS-CoV-2 infection in patients with a previous positive NST result (IgM and IgG sensitivity of 27.78% and 50.00%, respectively). These results are in contrast to those from Batra and colleagues ( Batra et al, 2020 ), who found that the test had a specificity of 100% and sensitivity of 99.1% for specimens collected >14 days post symptom onset or >5 days post-RNA testing. On the other hand, Meschi et al (2020) showed that the Abbott system could have lower sensitivity, which is more similar to our results (61.9% on the fourteenth day).…”
Section: Discussioncontrasting
confidence: 99%
“…There are now commercial serologic tests (immunochromatography) available, which are performed with whole blood and could be useful for diagnosis. 21 …”
Section: Discussionmentioning
confidence: 99%
“…Further reported sensitivities for the Abbott test are 99.1% in hospitalised patients(8), 97.9% in a mix of hospitalised patients and infected healthcare workers(9), 100% in patients, the vast majority of whom were hospitalised(10), 100 % in sera from patients whose disease severity was not specified(11) and 84.2% in patients admitted to a Singapore hospital, all of whom had respiratory symptoms and/or fever, but disease severity was not further reported(12). Reported sensitivities for the Roche test are 98.3% in sera from mostly hospitalised patients(13).…”
Section: Introductionmentioning
confidence: 99%